Зарубіжний досвід обгрунтування пріоритетних напрямів розвитку підприємництва - Дмитрієв, І.А. (Культура народов Причерноморья, 2013)
У статті розглянуто зарубіжний досвід обґрунтування пріоритетних напрямів розвитку підприємництва: виявлено основні бар’єри та напрями розвитку підприємництва в країнах з розвиненою економікою, країнах Східної Європи, що претендують на вступ до Європейського Союзу та країнах СНД. Обґрунтовано пріоритетні напрями розвитку підприємництва в Україні, виконання котрих забезпечить не лише вирішення наявних проблем розвитку малого підприємництва, а й попередження його майбутніх проблем. В статье рассмотрено зарубежный опыт обоснования приоритетных направлений развития предпринимательства: выявлены основные барьеры и направления развития предпринимательства в странах с развитой экономикой, странах Восточной Европы, претендующих на вступление в Европейский Союз и странах СНГ. Обосновано приоритетные направления развития предпринимательства в Украине, выполнение которых обеспечит не только решение существующих проблем развития малого предпринимательства, но и предупреждение его будущих проблем. In the article the foreign experience of the entrepreneurship development priority directions justification is considered: the main barriers and directions of the entrepreneurship development in the developed economies countries, the countries of Eastern Europe, applying for membership in the European Union and the countries of the CIS are identified. The priority directions of the entrepreneurship development in Ukraine (the implementation of which will provide not only a resolve of the existing problems of small business development, but also its future problems prevention) are justified. There are such directions as: legal framework improvement in the entrepreneurship field; regulatory policy formation; activation of the financial-credit and investment support for small businesses; establishment of the small business infrastructure; implementation of the regional policy promoting entrepreneurship development; tax policy improvement; creation of the information support system for entrepreneurship development; innovations promotion; education, retraining and qualification promotion of the staff specializing in the entrepreneurship field; support of the employment programs; development of youth, women's entrepreneurship, pensioners and disabled people entrepreneurship; promotion of the small businesses foreign trade.